Chimeric Antigen Receptor T Cells With Modified Interleukin-13 Preferentially Recognize IL13Rα2 and Suppress Malignant Glioma: A Preclinical Study - Kim, Kiwan; Gwak, Ho-Shin; Han, Nayoung; Hong, Eun Kyung; Choi, Beom K.; Lee, Sangeun; Choi, Soyoung; Park, Ju-Hwang; Seok, Ji-Hye; Jeon, Yeongha; Cho, Hyuntae; Lee, Song-Jae; et al. (Frontiers in Immunology, 2021)
Background: Interleukin-13 receptor α 2 (IL13Rα2) is a promising tumor-directed antigen of malignant glioma (MG). Here, we examine efficacy and safety of T cells containing a YYB-103 chimeric antigen receptor (CAR) that can preferentially bind to IL13Rα2 on MG cells. Methods: IL13 was modified on the extracellular domain by substitution of amino acids with E13K, R66D, S69D, and R109K and stably transfected into human T cells using a retroviral vector. The in vitro efficacy of YYB-103 CAR T cells was tested in cell lines with differing IL13Rα1 and IL13Rα2 expression. The in vivo efficacy of intracerebroventricular (i.c.v.) and intravenous (i.v.) routes of YYB-103 CAR T cell administration was tested in orthotopic MG mouse models. Immunohistochemical staining of MG was performed using 53 patient WHO grade 3/4 surgical specimens. IL13Rα2 expression was quantified by H-score calculated from staining intensity and percentage of positive cells. Results: Binding affinity assay of YYB-103 verified apparently nil binding to IL13Rα1, which was more selective than previously reported IL13 modification (E13Y). YYB-103 CAR T cells showed selective toxicity toward co-cultured U87MG (IL13Rα1+/IL13Rα2+) cells but not A431 (IL13Rα1+/IL13Rα2-) cells. Consistently, YYB-103 CAR T cells suppressed tumor growth in nude mice receiving orthotopic injection of U87 MG cells. Both i.c.v. and i.v. injection of YYB-103 CAR T cells reduced tumor volume and prolonged overall survival of tumor-bearing mice. The median H-score for IL13Rα2 in patient-derived MG tissue was 5 (mean, 57.5; standard deviation, 87.2; range, 0 to 300). Conclusion: This preclinical study demonstrates the efficacy of IL13Rα2-targeted YYB-103 CAR T cells against MG cells. The use of modified IL13 to construct a CAR facilitated the selective targeting of IL13Rα2-expressing MG cells while sparing IL13Rα1-expressing cells. Notably, YYB-103 CAR T cells exhibited effective blood-brain barrier crossing, suggesting compatibility with i.v. administration rather than intracranial injection. Additionally, the high H-score for IL13Rα2 in glioblastoma, especially in conjunction with the poor prognostic markers of wild-type IDH-1 and unmethylated MGMT, could be used to determine the eligibility of patients with recurrent glioblastoma for a future clinical trial of YYB-103 CAR T cells.